Transcription Profiling Reveals Cooperative Metabolic Interactions in a Microbial Cheese-Ripening Community Composed of Debaryomyces hansenii, Brevibacterium aurantiacum, and Hafnia alvei - Pham, Nguyen-Phuong; Landaud, Sophie; Lieben, Pascale; Bonnarme, Pascal; Monnet, Christophe (Frontiers in Microbiology, 2019)
Ripening cultures containing fungi and bacteria are widely used in smear-ripened cheese production processes, but little is known about the biotic interactions of typical ripening microorganisms at the surface of cheese. We developed a lab-scale mini-cheese model to investigate the biotic interactions of a synthetic community that was composed of Debaryomyces hansenii, Brevibacterium aurantiacum and Hafnia alvei, three species that are commonly used for smear-ripened cheese production. Transcriptomic analyses of cheese samples produced with different combinations of these three species revealed potential mechanisms of biotic interactions concerning iron acquisition, proteolysis, lipolysis, sulfur metabolism and D-galactonate catabolism. A strong mutualistic interaction was observed between H. alvei and B. aurantiacum. We propose an explanation of this positive interaction in which B. aurantiacum would benefit from siderophore production by H. alvei, and the latter would be stimulated by the energy compounds liberated from caseins and triglycerides through the action of the proteases and lipases secreted by B. aurantiacum. In the future, it would be interesting to take the iron acquisition systems of cheese-associated strains into account for the purpose of improving the selection of the ripening culture components and their association in mixed cultures.